2013
DOI: 10.1002/j.2161-1912.2013.00025.x
|View full text |Cite
|
Sign up to set email alerts
|

Racism‐Related Stress, General Life Stress, and Psychological Functioning Among Black American Women

Abstract: The relationship between general life stress, perceived racism, and psychological functioning was explored in a sample of 118 Black American women. Findings indicate that racism‐related stress was not a significant predictor of psychological functioning when controlling for general life stress. Perceived racism was positively associated with general life stress. Implications for practice and future research are discussed. La relación entre el estrés general de la vida, el racismo percibido y el funcionamiento … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…Although the exposure perspective can account for some group differences in the stress-health relationship, researchers note that while holding stress at equal levels, some groups (e.g., women, the poor, and racially underrepresented groups) still report higher levels of psychological distress (McLeod & Kessler, 1990;Thoits, 1984Thoits, , 2010. Conversely, the vulnerability perspective begins with the assumption that stress alone cannot account for social group differences in psychological distress, but rather it is the mediators (e.g., mastery, selfesteem, and social support) that govern the effects of stressors (Kessler, 1979;Pieterse, Carter, & Ray, 2013;Thoits, 2010). Because our research is guided by Pearlin's stress-support-distress framework, our conceptual model (see Figure 1) accounts for exposure to stress (i.e., the quantity and source of stress), vulnerability to stress (i.e., perceptions of social support adequacy), and the manifestation of stress (i.e., psychological distress).…”
Section: Stress and Health For Black Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exposure perspective can account for some group differences in the stress-health relationship, researchers note that while holding stress at equal levels, some groups (e.g., women, the poor, and racially underrepresented groups) still report higher levels of psychological distress (McLeod & Kessler, 1990;Thoits, 1984Thoits, , 2010. Conversely, the vulnerability perspective begins with the assumption that stress alone cannot account for social group differences in psychological distress, but rather it is the mediators (e.g., mastery, selfesteem, and social support) that govern the effects of stressors (Kessler, 1979;Pieterse, Carter, & Ray, 2013;Thoits, 2010). Because our research is guided by Pearlin's stress-support-distress framework, our conceptual model (see Figure 1) accounts for exposure to stress (i.e., the quantity and source of stress), vulnerability to stress (i.e., perceptions of social support adequacy), and the manifestation of stress (i.e., psychological distress).…”
Section: Stress and Health For Black Womenmentioning
confidence: 99%
“…Because of Black women's marginalized position in the social structure, they are exposed to many structural factors such as poverty, low education, racism, and violence (Bauboeuf-Lafontant, 2007;Pieterse et al, 2013;Terhune, 2008). Consequently, they often lack the economic and political personal resources that can mitigate many of the negative psychological effects of stress (Hine, 2007;Lincoln et al, 2005).…”
Section: Stress and Health For Black Womenmentioning
confidence: 99%
“…Racial discrimination can be a daily part of life for many minorities. [21][22][23] Several studies have found that frequency of racial discrimination may vary among minority groups. [23][24][25] It is unclear whether certain groups are targeted more than others, or if there are other factors associated with the ability to detect racial discrimination events.…”
mentioning
confidence: 99%
“…To assess participant changes in awareness of White privilege, we used the White Privilege Attitudes Scale (WPAS; Pinterits, Poteat, & Spanierman, 2009). The WPAS is a 28-item scale that assesses the multidimensional nature of White privilege attitudes, including affective, cognitive, and behavioral dimensions, and is scored on a 6-point Likert scale ranging from 1 (strongly disagree) to 6 (strongly agree), with higher scores indicating higher White privilege attitudes.…”
Section: Methodsmentioning
confidence: 99%